Marginality and Resistance in M. G. Sanchez’s Jonathan Gallardo: A Postcolonial Reinterpretation of Gibraltar - Barbuto, Ilaria (Margins/Marges/Margini, 2025)
This paper presents an analysis of the novel Jonathan Gallardo (2015) by M. G. Sanchez, situated within the context of postcolonial studies and spatial theory. The primary objective of this analysis is to demonstrate how marginality – understood in social, spatial, and psychological terms – assumes both epistemological and political functions within the text. The novel offers a perspective from the periphery, characterised as a privileged vantage point. Practices of resistance, forms of identity reappropriation, and processes of rewriting collective memory emerge from this peripheral standpoint. The methodology employed is interdisciplinary, integrating theoretical tools derived from sociology, postcolonial criticism, and geocriticism. A comprehensive examination of the concepts of “marginal man,” post-imperial marginality, and “hauntology” is imperative, as these concepts are instrumental in elucidating the representation of the protagonist and the urban space of Gibraltar as locales characterised by historical, cultural, and symbolic tensions. The investigation demonstrates how Jonathan Gallardo stages a marginal subjectivity, capable of intercepting the voices of the colonial past and the prefigurations of an uneasy future. Gibraltar emerges as a liminal context, geographically peripheral and historically displaced, where marginality becomes a tool for critical awareness and a potential agent of transformation. The findings support the assertion that the work functions as a postcolonial counter-narrative, through which Gibraltar asserts its entitlement to narrate itself from an autonomous perspective. Consequently, literature serves as a vehicle for symbolic resistance and a means of reconstituting collective identity from a post-imperial perspective.